Biomaterials developments for brain tissue engineering - Oliveira, Maria Eduarda Moreira Pinheiro Santos (2018)
The Central Nervous System (CNS) is a highly complex organ that works as the control centre of the body, managing vital and non-vital functions. Neuro-diseases can lead to the degeneration of neural tissue, breakage of the neuronal networks which can affect vital functions and originate cognitive deficits. The complexity of the neural networks, their components and the low regenerative capacity of the CNS are on the basis for the lack of recovery, having the need for therapies that can promote tissue repair and recovery. Most brain processes are mediated through molecules (e.g. cytokines, neurotransmitters) and cells response accordingly and to surrounding cues, either biological or physical, which offers molecule administration and/or cell transplantation a great potential for use in brain recovery. Biomaterials and in particular, of natural origin are attractive candidates owed to their intrinsic biological cues and biocompatibility and degradability. Through the use of biomaterials, it is possible to protect the cells/molecules from body clearance, enzymatic degradation while maintaining the components in a place of interest. Moreover, by means of combining several components, it is possible to obtain a more targeted and controlled delivery, to image the biomaterial implantation and its degradation over time and tackling simultaneously occurring events (cell death and inflammation) in brain diseases. In this chapter, it is reviewed some brain-affecting diseases and the current developments on tissue engineering approaches for a functional recovery of the brain from those diseases.